BIOEQUIVALENCE: HEALTH, COMMERCIAL AND POLITICAL IMPLICATIONS OF THIS TECHNICAL TOOL - Rosa Maria Vera; Marcelo Estrin; Gustavo H. Marin (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Bioequivalence (BE) is a clinical-pharmacological research method that has acquired great relevance in most of the countries due to its health, commercial, and political importance. Some regulatory agencies require routine BE for all products registered in their national territory, while others opt for policies that require this study only for certain products. The truth is that even today there are current debates about its definition, its clinical relevance and the level of requirements that each country must ask to those companies that aim to register a new product. The objective of this paper is to provide different perspectives on the concept of bioequivalent drugs, establish what are the advantages or disadvantages of adopting different policies on BE, identify the interests associated with this concept and clarify its real importance for public health.